Satellite observed indicators of the maximum plant growth potential and their responses to drought over Tibetan Plateau (1982–2015). (January 2020) - Li, Jialing; Wu, Chaoyang; Wang, Xiaoyue; Peng, Jie; Dong, Donglin; Lin, Gang; Gonsamo, Alemu
Highlights: The timing and the absolute value of the maximum NDVI in summer were analyzed over TP during 1982–2015. A higher SPEI led to a later POS and significantly enhanced NDVImax in summer. An annual precipitation around 550 mm seemed to be a threshold separating the positive and negative impacts of drought on NDVImax . Abstract: The maximum plant growth potential in summer plays an important role in regulating annual carbon balance. However, indicators of plant growth at this stage are not well established. With high elevations on the Tibetan Plateau (TP), terrestrial ecosystems in this region are vulnerable to climate change and in particular, the frequently and intensified droughts as projected by ecosystem models. To better understand the maximum plant growth potential and its response to drought over the past three decades (1982–2015), we analyzed the impacts of drought, as indicated by the Standardized Precipitation-Evapotranspiration Index (SPEI), on two derived indicators of the maximum summer growth of plants, including the timing and the absolute value of the maximum Normalized Difference Vegetation Index (referred as the peak of growing season, POS and NDVImax, respectively). We found that both temporal and spatial patterns of SPEI, POS and NDVImax showed high spatial heterogeneity over TP. A higher SPEI led to a later POS for about 57% of regions but it reversed for the alpine sparse vegetation roughly account for 3.5% of all pixels, probably due to water availability of this plant functional type. For NDVImax, we found a significantly enhanced NDVImax in summer for a higher SPEI over 70% of significant pixels, irrespective of differences among plant functional types. We further analyzed these correlations by temperature and precipitation gradients and found that an annual precipitation around 550 mm seemed to be a threshold separating the positive and negative impacts of drought on NDVImax . These results would be useful to better comprehend the impacts of drought on ecosystem response in a changing climate in future.